Theme and Thematic Progression in EFL Students’ Writing: A Systemic Functional Linguistics Analysis - Tarigan, Fatin Nadifa; Zahiri, Arsi (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2025)
A key component of writing that seamlessly integrates into language events is the use of theme and thematic progression. Observing themes is valuable for identifying the writing challenges faced by English learners, while incorporating thematic progression into writing lessons can help students achieve greater coherence in their texts. The present study aims to investigate the dominant patterns of theme and thematic progression in the writing of EFL college students at Universitas Pembinaan Masyarakat Indonesia (UPMI), Medan. A qualitative approach was employed since the study primarily focuses on descriptive elaborations of students’ writing assignments. Data were collected through purposive sampling, involving twenty-one undergraduate students from the Faculty of Teacher Training and Education (FKIP) at UPMI who were enrolled in academic writing classes. Both classroom observations and semi-structured interviews served as the instruments for data collection. Data analysis consisted of several stages. First, the students’ pre-writing assignments were reviewed and categorized into three levels: low, middle, and high achievers. These texts were then analyzed using the framework of Systemic Functional Linguistics (SFL), particularly the theory of theme systems and thematic progression. Subsequently, the students’ post-writing assignments were examined and compared within the same categorization. The findings reveal a significant relationship between students’ writing performance and the application of the SFL framework. High- and middle-achieving students demonstrated the ability to construct coherent messages within clauses, effectively employing theme systems and thematic progression to produce larger texts characterized by cohesion and coherence. This suggests that explicit attention to thematic progression in writing pedagogy can play a crucial role in improving the academic writing skills of EFL learners, particularly in the Indonesian higher education context.